Molecular detection and identification of Enterococcus faecium isolated from dental root canals - Mustafa, Eman A.; Hamdoon, Suhad M.; Shehab, Enas Y. (Iraqi Journal of Science, 2021)
Enterococci are usually encountered and predominate in oral infections, especially those associated with dental root canal infections of necrotic pulp and periodontitis. This study aimed to detect and identify Enterococcus faecium isolated from infected root canals, using polymerase chain reaction ( PCR). Thirty samples were collected from patients with necrotic pulp, infected root canals, and endodontic treatment failure, attending the Conservative Treatment Department, College of Dentistry, Mosul University, Dental Teaching Hospital. The samples were obtained by inserting sterile paper points into the root canals and transferred in brain heart infusion broth vials to be inoculated in a selective M-Enterococcus Agar Base . Twenty five isolates that belong to the genus Enterococcus were recognized by traditional culture methods and biochemical tests. Then, DNA extractions of these isolates were carried out for identification with PCR by the amplification of ddI (D-Ala-D-Ala Ligase) chromosomal genes of Enterococcus faecium. Among the 25 isolates, twenty (80%) were identified to the level of Enterococcus faecium by traditional culture methods and biochemical tests, in comparison to 17 (68%) identified by molecular identification. The PCR products for the specific primer produced bands on agarose gel at the position of 658bp. The study showed that the use of PCR with primers for the E. faecium ddI gene may be the most accurate method for rapid identification of Enterococci. Molecularidentification of Enterococcus spp. revealed a significant role of E. feacium in root canal infections. Also, the detection of ddI gene using PCR provides a definitive target that could be used for the detection of E. faecium from clinical samples.